Sintesis Senyawa Aurivillius Lapis Empat PbBi4Ti4O15 dan PbBi3NdTi4O15 dengan Metode Lelehan Campuran Garam NaCl-KCl dan Karakterisasi Struktur - Wibowo, Gita Rachmad; Emriadi, Emriadi; Zulhadjri, Zulhadjri (Universitas Andalas, 2019)
Four-layered Aurivillius phases PbBi4Ti4O15doped with Nd3+ with formula PbBi3NdTi4O15 were synthesized by molten-salt technique using NaCl and KCl (1:1 molar ratio) as the flux. Precursors were weighed stoichiometrycally and grinded with salts mixture in 1:7 ratio (product : salts mixture) until homogenous. The samples were heated at temperature 600oC, 700oC, 800oC, and 900oC for 5 hours for each temperature. The products were characterized by X-ray diffractometer (XRD), Scanning Electron Microscope (SEM) and LCR-meter. XRD data were refined by Rietica program using Le Bail technique. Refinement results showed the best structure as the A21am of space group for both samples. Surface analysis for each samples morphology is the plate-like by SEM characterization. Dielectric constants measured at room temperature show that the sample doped Nd3+ has lower value than sample without containing Nd3+ cation.